Ceramics and the Spanish conquest : response and continuity of Indigenous pottery technology in Central Mexico - Hernández Sánchez, Gilda (Early Americas ;, 2012)
Focusing on the native ceramic technology of central Mexico during the early colonial period and the present-day, this book offers a refreshing view into the process of cultural continuity and change in the Indigenous Mesoamerican world after the Spanish ...